SPORT HAS NO GENDER (Fiep Bulletin - online, 2017)
We are experiencing major transformations today and among them are strongly inserted the respect for diversity andthe right to equal choices and living conditions. The present article was produced from the data obtained in an intervention reportapplied in a private school in Maceió, Alagoas, with students from the 9th grade of Elementary School II, whose purpose was topromote a reflection about respect for diversity using as a facilitator Of relations to sports practice. Sports activities were carriedout in the Futsal and Queimada modalities to encourage boys and girls to carry out activities together. With the accomplishment ofthe proposed activities it was possible to perceive a beginning of reflection in the students and the acceptance of the differencesand the choices made independently of the regimes followed by the conservative society.
Keywords: Diversity; Sport; Education